In vitro determination of optimal antifungal combinations against Cryptococcus neoformans and Candida albicans. - Ghannoum, M A (1995)
There is currently no rapid, reliable, and reproducible in vitro technique to describe the growth-inhibitory interactions of antifungal drug combinations over a wide range of drug concentrations. We have developed a microdilution plate assay that was used to determine optimal drug combinations and concentrations of one-, two-, and three-drug regimens of amphotericin B (AmphB), fluconazole (FLU), and 5-fluorocytosine (5FC) for growth inhibition of three isolates each of Cryptococcus neoformans and Candida albicans. These growth inhibition data were then used in a multifactorial design technique to (i) generate contour and surface response plots to aid visual interpretation and (ii) develop mathematical equations describing the growth responses of the fungi to a wide range of antifungal concentrations and ratios. Our data indicated that (i) antifungal drug-drug interactions affecting yeast growth are complex functions of the drugs used in combination, their absolute concentrations, and also their relative (proportional) concentrations; (ii) AmphB-FLU combinations had additive effects against C. albicans over wide concentration ranges for each agent but were indifferent (i.e., were less than additive) in their inhibitory effect on C. neoformans; (iii) other two-drug combinations (FLU-5FC or AmphB-5FC) had indifferent effects on the growth of both fungi; and (iv) three-drug combinations (AmphB-FLU-5FC) showed an additive inhibitory effect on the growth of both C. albicans and C. neoformans. The finding that no antagonism was observed in combinations employing AmphB and FLU in this in vitro model is of critical importance since it argues against the current theoretical concept, based on the individual drug's mode of action, of antagonism between these two drugs. These microdilution techniques provide a method to determine rational regimens of antifungal agents in multidrug combinations for future testing to correlate in vitro activity with in vivo response. The use of this approach has made the evaluation of complex antifungal drug-drug interactions possible and provided important new information to the evolving field of antifungal drug combination.